Basic Sciences in Anesthesia (Springer International Publishing, 2018)
This textbook presents the most recent evidenced-based knowledge in basic sciences in anesthesia. It covers topics from the syllabus of the American Board of Anesthesiology (ABA) basic science exam, including anatomy, pharmacology, physiology, physics in anesthesia, and more. In each chapter, key points summarize the content, followed by a pertinent and concise discussion of the topic, ending with multiple choice questions with answers and suggested further reading. Basic Sciences in Anesthesia is aimed at residents taking the ABA basic science of anesthesia examination, and any other anesthesiologist or trainee with an interest in the topic.